Managing Earnings Using An Insurance Subsidiary: A Case of Restraint by Sears/Allstate. - Weil, Roman L. (The Accounting Review, 1980)
ABSTRACT: This note reports on one method currently available to insurance companies and those with insurance subsidiaries for "managing earnings," illustrates it for Sears Roebuck and Co., and concludes that Sears' management has not taken advantage of all of the income-smoothing possibilities provided by the generally accepted accounting principles for insurance companies.